Deposition of Pd nanoparticles on MWCNTs: Green approach and application to hydrogen sensing - Yoo, Il Han; Kalanur, Shankara S.; Seo, Hyungtak (Journal of Alloys and Compounds, 2019)
A facile and green method is proposed for the deposition of palladium nanoparticles (NPs) on multiwalled carbon nanotube (MWCNT) thin films. Reduction and deposition of Pd NPs are achieved via oxidation of methanol on CNT supports under UV light irradiation. The proposed process yields uniformly distributed and highly crystalline Pd NPs on MWCNTs. When Pd-MWCNT thin films are exposed to hydrogen gas, H2 is adsorbed onto the Pd surface and spills over, followed by stable C–H bond formation via chemisorption of H atoms on the MWCNTs, resulting in increased electrical resistance due to widening of the band gap. As an electrical sensor, Pd-MWCNTs can detect H2 gas within a concentration range of 0.0004–80% in air at room temperature with a rapid response and quick recovery. Importantly, the proposed photochemical method can be extended to deposition of Pd NPs on thin films of other materials.
Keywords: Concentration ranges; Electrical resistances; Hydrogen sensor; Methanol Oxidation; Oxidation of methanol; Palladium nanoparticles; Photochemical method; UV irradiation; Electrical resistance; Hydrogen sensor; Methanol oxidation; Multiwalled carbon nanotubes; Palladium; UV irradiation